A faculty member learning with and from an undergraduate teaching assistant: Critical reflection in higher education - Daniello, Frank; Acquaviva, Caroline (International Journal for Students as Partners, 2019)
This case study describes a student-faculty partnership between an undergraduate teacher education student and a faculty member of teacher education. This faculty-centric partnership aimed to enhance the faculty member’s critical reflection on his pedagogy in an introduction to teacher education course. In this jointly-written article, we offer student and faculty insights about the process we employed, the outcomes of our teaching and learning together, and the complexities of student-faculty working relationships stemming from power dynamics. We also provide recommendations for faculty and students looking to engage in collaborations. These recommendations center on defining partner roles, using video recordings, and addressing power dynamics between students and faculty within higher education. Drawing from our experience, we suggest that student-faculty partnerships are one fruitful avenuefor improving the quality of instruction in higher education. They require minimum financial resources and can enhance faculty pedagogy, which will benefit current and future students.